2001
DOI: 10.1002/ajmg.1500
|View full text |Cite
|
Sign up to set email alerts
|

An interactive computer program can effectively educate patients about genetic testing for breast cancer susceptibility

Abstract: As genetic testing for susceptibility to breast cancer becomes more widespread, alternative methods for educating individuals prior to testing will be needed. Our objective was to compare face-to-face education and counseling by a genetic counselor with education by an interactive computer program, assessing the effects of each on knowledge of breast cancer genetics and intent to undergo genetic testing. We used a randomized, controlled trial. Seventy-two self-referred women with a first-degree relative with b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
123
3
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 121 publications
(130 citation statements)
references
References 39 publications
(32 reference statements)
3
123
3
1
Order By: Relevance
“…For example, all 9 trials evaluating knowledge have shown that decision aids significantly improve patient knowledge, with a weighted mean difference of 19% (compared with 16% in this trial). 8,[12][13][14][15][16][17][18][19][20] Similarly, all 6 of the trials that examined decisional conflict reported statistically significant improvements with decision aids of magnitudes virtually identical to our results. 17,18,[21][22][23][24] However, decision aids have had variable impacts on management in the 3 tri- als evaluating medical therapies: one 24 reported a 76% increase in hepatitis B vaccination with a decision aid, another 25 reported a nonsignificant 8% reduction in hormone replacement use, and the third 17 reported a nonsignificant 6% increase in ASA use among patients with NVAF at low risk of stroke.…”
Section: Discussionsupporting
confidence: 81%
“…For example, all 9 trials evaluating knowledge have shown that decision aids significantly improve patient knowledge, with a weighted mean difference of 19% (compared with 16% in this trial). 8,[12][13][14][15][16][17][18][19][20] Similarly, all 6 of the trials that examined decisional conflict reported statistically significant improvements with decision aids of magnitudes virtually identical to our results. 17,18,[21][22][23][24] However, decision aids have had variable impacts on management in the 3 tri- als evaluating medical therapies: one 24 reported a 76% increase in hepatitis B vaccination with a decision aid, another 25 reported a nonsignificant 8% reduction in hormone replacement use, and the third 17 reported a nonsignificant 6% increase in ASA use among patients with NVAF at low risk of stroke.…”
Section: Discussionsupporting
confidence: 81%
“…[13][14][15][16] The included trials were conducted in 4 countries and published between 1997 and 2009 (see Table 1). The trials focused on decisions related to: hormone replacement therapy, 17,18 breast cancer genetic testing 19,20 and treatment, 21 prostate cancer screening 22 and treatment, 23 prenatal testing, 24 schizophrenia treatment, 25 and menorrhagia treatment. 26 The mean number of participants per trial was 242 (range 43-625).…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…29 Subsequently, we revised and updated the computer program and conducted a larger, randomized, multicenter trial among women referred for genetic counseling due to family or personal histories of breast cancer. 30 In this article, we report findings from one aspect of that study that compared the effectiveness of counseling alone with counseling preceded by computer use.…”
mentioning
confidence: 99%